High thermal stability effect of vanadium on the binary CuAl base alloy for a novel CuAlV high-temperature shape memory alloy - Karaduman, Oktay; Ozkul, Iskender; Guler, Seval Hale; Canbay, Canan Aksu (Walter de Gruyter Gmbh, 2024)
In this study, two high-temperature shape memory alloys (HTSMAs) of CuAlV with unprecedented chemical compositions were fabricated using the arc melting technique, followed by traditional ice-brine water quenching after the melting process. To characterize the shape memory properties and structure of the alloys, a series of tests including differential calorimetry (DSC and DTA), EDS, optical microscopy, and XRD were conducted. The DSC tests, performed at different heating and cooling rates, demonstrated highly stable reversible martensitic phase transformation peaks at high temperatures, which were also confirmed by the results of DTA tests. Microstructural XRD and optical microscopy tests were conducted at room temperature, revealing the martensitic structure of the alloys in both cases. Based on all the results, the effects of different minor amounts of vanadium additives directly on the CuAlV alloy were discussed.
Keywords: CuAl-based HTSMA; vanadium addition; shape memory effect; martensitic transformation; DSC; DTA